Electronic and Optical Properties of Alkaline Earth Metal Fluoride Crystals with the Inclusion of Many-Body Effects: A Comparative Study on Rutile MgF2 and Cubic SrF2 - Cappellini, Giancarlo; Furthmueller, Juergen; Bechstedt, Friedhelm; Botti, Silvana (Symmetry, 2023)
We conducted a systematic investigation using state-of-the-art techniques on the electronic and optical properties of two crystals of alkaline earth metal fluorides, namely rutile MgF (Formula presented.) and cubic SrF (Formula presented.). For these two crystals of different symmetry, we present density functional theory (DFT), many-body perturbation theory (MBPT), and Bethe–Salpeter equation (BSE) calculations. We calculated a variety of properties, namely ground-state energies, band-energy gaps, and optical absorption spectra with the inclusion of excitonic effects. The quantities were obtained with a high degree of convergence regarding all bulk electronic and optical properties. Bulk rutile MgF (Formula presented.) has distinguished ground-state and excited-state properties with respect to the other cubic fluoride SrF (Formula presented.) and the other members of the alkaline earth metal fluoride family. The nature of the fundamental gaps and estimates of the self-energy and excitonic effects for the two compounds are presented and discussed in detail. Our results are in good accordance with the measurements and other theoretical–computational data. A comparison is made between the excitation and optical properties of bulk rutile MgF (Formula presented.), cubic SrF (Formula presented.), and the corresponding clusters, for which calculations have recently been published, confirming strong excitonic effects in finite-sized systems.
CRIS-Team Scopus Importer:2023-04-20
Keywords: crystal symmetry; DFT theory; electronic and optical properties; fluoride compounds; quasiparticle and excitonic effects; UV crystal materials